Pengaruh Gaya Kepemimpinan, Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan Dengan Sistem Reward Sebagai Variabel Pemoderasi (Studi Empiris Pada Pt. Telkom Akses Solo) - Sejati, Diska Wahyu; , Dr. Fatchan Achyani, S.E, M.Si (2017)
This research aims to analyze the influence of leadership styles, organizational culture and organizational commitment to employee performance with reward system as a moderating variable. Population of this research is PT. Telkom Akses Solo. The number of samples is 50 employees. The method used is Random Sampling Method with the type of Convenience Sampling. The analysis of the data used is Moderated Regression Analysi to test the moderating variables. Research results indicate that the variable leadership styles and organization culture not effect the employee performance. While variable organizational commitment and reward system effect the employee performance. research results also that the reward system proved not able to moderate the influence og leadership style and organization culture the employee performance. But the reward system able to moderated organizational commitment to employee performance.